Toward Representational Sovereignty: Rewards and Challenges of Indigenous Media in the A’uwẽ-Xavante Communities of Eténhiritipa-Pimentel Barbosa - Laura R. Graham (Media and Communication, 2016)
Focusing on the communities of Eténhiritipa-Pimentel Barbosa of eastern Mato Grosso, Brazil, this article considers the tremendous shift that has taken place over the last twenty-five years in A’uwẽ-Xavante peoples’ use of audio-visual media to achieve greater representational sovereignty. It discusses the adoption of video in the context of A’uwẽ-Xavante ideologies and gendered patterns of dealing with the outside and their prior use of cassette technology. This case demonstrates that, while the adoption of new media has not proven to be the final assault in a Faustian bargain with modernity, media makers face a number of significant challenges and dilemmas, specifically curating, archiving, and also securing and sustaining financial and technological support. Partnerships and collaborations are essential but their often-precarious nature presents difficulties. Dedication, persistence, creativity and adaptability are assets community members draw upon in responding to challenges. Media makers are increasingly gaining more control and are now training the next generation of youths; young people are using new social media, as well as video and film, to achieve greater representational sovereignty.